Sinkretisme Islam Dan Budaya Jawa Dalam Upacara Bersih Desa Di Purwosari - Dewi , Arlinta Prasetian (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The goal of this paper is to get a better insight into the phenomenon of bersih desa ritual performed by members of the community in Purwosari, kabupaten Ponorogo, using phenomenological approach. Bersih desa ritual connotes one of the ancestral heritages, which is replete with symbols and activities that maintain the harmony between Islam and Javanese culture. The symbols not only mean the thanksgiving expression but also tolak balak (English: the antidote to disaster) by performing several rituals and offerings which are packaged in a series of events. Islam and Javanese hence combine, resulting in the syncretism of kejawen (English: Javanese) Islamic culture that is a repertoire of traditions and culture.